Contemporary financial management - Moyer, R. Charles; Mcguigan, R James; Rao, Ramesh P. (Cengage Learning, 2015)
Providing an introduction to financial management, this book focuses on value creation, risk management, and effectively managing cash flows, the international aspects of financial management, the ethical context of managerial decision-making, and the increased impact of the Internet in business practice.